Transport and Metabolism of Indole-3-Acetic Acid in Coleus Petiole Segments of Increasing Age - Veen, Henk (1969)
Transport and metabolism of IAA-1-(14)C in Coleus blumei Benth. was studied by means of a combination of liquid scintillation counting, autoradiography and thin-layer chromatography. Transport of IAA in petiole segments of increasing age (No. 2-8) was strictly polar in a basipetal direction. No acropetal movement occurred in either young or old tissues. The greatest amount, expressed as a percentage of the radioactivity lost from the donor block, was found in basal receivers on petiole number 2. There was gradually less transport in older segments. The recovery as a percentage of the radioactivity not accounted for by donor and receiver blocks, measured by counting the radioactivity in an acetonitrile-extract of petiole segments, was low: 25 to 50%. In this acetonitrile-soluble fraction evidence for different radioactive compounds was found, depending on the age of the tissue. A possible relationship between the amounts of auxin transported in the tissue and its corresponding metabolism is discussed.